Ibn Taymiyya og de guddommelige egenskaber - Bramsen, Dorthe (Religionsvidenskabeligt Tidsskrift, 2003)
According to Islamic theology God is transcendent and different to anything created. There are many verses in the Qur’ân, however, which describe God in almost anthropomorphic terms. He is described as talking and as sitting on the heavenly throne. Throughout history Muslim traditionalists have claimed that these verses must not be interpreted. They are to be accepted as true in their own sense. If the Qur’ân describes God as talking and as sitting on the heavenly throne, then He is actually talking and sitting on the heavenly throne. <p class="MsoNormal" style="margin: 0cm 0cm 0pt 14.2pt; line-height: normal; tab-stops: 14.2pt 1.0cm 42.55pt 2.0cm 70.9pt 3.0cm 99.25pt 4.0cm 127.6pt 5.0cm 155.95pt 6.0cm 184.3pt 7.0cm 212.65pt 8.0cm 241.0pt 9.0cm 269.35pt 10.0cm 297.7pt 11.0cm;">This article examines the teaching of one of the most celebrated traditionalists of the Hanbalî school, Taqî al-Dîn Ahmad ibn Taymiyya (d. 1328). In 1306 Ibn Taymiyya was accused of anthropomorphism and sentenced to imprisonment on the ground that he taught that the descriptions of God in the Qur’ân are true in reality. The article examines Ibn Taymiyyas defence against the allegations of anthropomorphism and it demonstrates that Ibn Taymiyyas teaching was most of all an attempt to unite the dogma of God’s transcendence with the teaching that the descriptions of God in the Qur’ân are true.